UNDERSTANDING SOCIAL ENTERPRISES IN INDONESIA: DRIVERS AND CHALLENGES - Rokhima Rostiani; Widya Paramita; Handini Audita; Risa Virgosita; Teguh Budiarto; Boyke R. Purnomo (Journal of Indonesian Economy and Business (JIEB), 2014)
Entrepreneurship has been one of the biggest growth topics in the past decades. Some entrepreneurs engage in socially active activities that are strongly embedded in their entrepreneurial activities and are known as social entrepreneurship. This research maps the presence of social enterprises in Indonesia by investigating the personal and organizational contexts of the social entrepreneurs. Qualitative research was conducted by engaging in in-depth interviews with 8 social enterprises in Indonesia. The findings of this research result in a unique and interesting map of the presence of the social entrepreneurs that contributes significantly to the extant literatures of social entrepreneurship.